2021
DOI: 10.1186/s42836-021-00093-5
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learnt from the impact of COVID-19 on arthroplasty services in Hong Kong: how to prepare for the next pandemic?

Abstract: Background Arthroplasty services worldwide have been significantly disrupted by the pandemic of coronavirus disease 2019 (COVID-19). This retrospective comparative study aimed to characterize its impact on arthroplasty services in Hong Kong. Methods From January 1 to June 30, 2020, the patients of “COVID-19 cohort” underwent elective total hip or knee replacement in Hong Kong public hospitals. The cohort was compared to the “control cohort” during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…A recent analysis of COVID-19 effects on arthroplasty Hong Kong Med J 2024;30:56-61 https://doi.org/10.12809/hkmj2210209 services in Hong Kong showed large (>50%) decreases in elective arthroplasties and surgical volume from January to June 2020. 4 Although the rate of revision operations remained similar during this period, the number of primary arthroplasty operations decreased by 91%, emphasising the importance of effective non-surgical treatment options for knee OA. 4 The multifactorial aetiology and slow progression of knee OA enable implementation of diverse therapeutic regimens.…”
Section: Overview Of Knee Osteoarthritis Treatment During Coronavirus...mentioning
confidence: 86%
See 1 more Smart Citation
“…A recent analysis of COVID-19 effects on arthroplasty Hong Kong Med J 2024;30:56-61 https://doi.org/10.12809/hkmj2210209 services in Hong Kong showed large (>50%) decreases in elective arthroplasties and surgical volume from January to June 2020. 4 Although the rate of revision operations remained similar during this period, the number of primary arthroplasty operations decreased by 91%, emphasising the importance of effective non-surgical treatment options for knee OA. 4 The multifactorial aetiology and slow progression of knee OA enable implementation of diverse therapeutic regimens.…”
Section: Overview Of Knee Osteoarthritis Treatment During Coronavirus...mentioning
confidence: 86%
“…4 Although the rate of revision operations remained similar during this period, the number of primary arthroplasty operations decreased by 91%, emphasising the importance of effective non-surgical treatment options for knee OA. 4 The multifactorial aetiology and slow progression of knee OA enable implementation of diverse therapeutic regimens. Non-surgical treatments can be broadly divided into non-pharmacological (preferred) and pharmacological options (Fig).…”
Section: Overview Of Knee Osteoarthritis Treatment During Coronavirus...mentioning
confidence: 86%
“…In a study done in another tertiary care centre in a different region of the same country, it was found that there was a reduction of 62.6% in the number of orthopaedic-related trauma cases during the lockdown period [ 12 ]. According to a study done in Hong Kong, there was a 53% reduction in elective joint replacement procedures from January to June 2020 [ 13 ]. The number of orthopaedic patients waiting for surgery has dramatically increased as a result of elective surgery cancellations and postponements.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey, the American Association of Hip and Knee Orthopedic Surgeons (AAHKS) estimates that hospitals stopped 92% of all elective surgeries [ 3 ]. However, a study from Hong Kong reports, for the period January to June 2020, a 53% reduction in elective joint replacement operations [ 17 ].…”
Section: Discussionmentioning
confidence: 99%